Disclosure of Environmental Violations and the Stock Market in the Republic of Korea - Dasgupta, Susmita; Hong, Jong Ho; Laplante, Benoit; Mamingi, Nlandu (World Bank, Washington, D.C., 2013)
For almost 20 years, the Ministry of Environment of the Republic of Korea has published on a monthly basis a list of enterprises that fail to comply with national environmental laws and regulations. In this paper, the authors examine the reaction of investors to the publication of these lists and show that enterprises appearing on these lists have experienced a significant decline in their market valuation. Firms in developing countries are often said to have no incentives to invest in pollution control because they typically face weak monitoring and enforcement of environmental regulations. The findings of the authors, however, indicate that the inability of formal institutions to control pollution through fines and penalties may not be as serious an impediment to pollution control as is generally argued. Environmental regulators in developing countries could harness market forces by introducing structured programs to release firm-specific information about environmental performance.